The effects of dieting and weight loss on neuroendocrine responses to tryptophan, clonidine, and apomorphine in volunteers. Important implications for neuroendocrine investigations in depression. - Goodwin, G; Fairburn, C; Cowen, P (1987)
The increases in the growth hormone (GH) level following intravenous infusion of the 5-hydroxytryptamine precursor tryptophan, the alpha 2-adrenoceptor agonist clonidine hydrochloride, and subcutaneous injection of the dopamine agonist apomorphine hydrochloride were determined in volunteers before and in the third week of a weight-reducing diet (1200 kcal/d). The increases in the prolactin level following intravenous infusion of tryptophan and in response to protirelin were also determined. In male subjects, the GH responses to tryptophan and apomorphine were markedly increased by dieting; while also significantly increased, the GH responses to clonidine were much less affected. Female subjects showed similar trends in the GH responses to tryptophan and clonidine. In male subjects, prolactin responses to tryptophan and protirelin were not increased by dieting. In females, the prolactin response to protirelin was similarly not increased, but the prolactin response to tryptophan was markedly enhanced. These results are relevant to the use of neuroendocrine tests in depression. In addition, they suggest different effects of weight loss on neurotransmitter function in men and women.